Sledovanie premorenia bratislavských psov Francisella tularensis - Gurycová, D; Kopcok, M (Veterinarni medicina, 1992)
Out of 548 serologically investigated dogs from Bratislava and other regions of Slovakia and Moravia, antibodies to F. tularensis were found in 16.4% (Tabs. I, II). In all the investigated groups of dogs from the region of Bratislava the highest seroprevalence by F. tularensis was recorded in watch dogs kept on farms and in cooperatives--37.5% and in rambling dogs--20.7% (Tab. I). The highest seropositivity was found in one to three year old dogs--22.2% (Tab. III). A similar degree of seroprevalence was also observed in one to three years old police dogs which came from the endemic region of tularemia--West Slovakia (19.3%) and East Slovakia (25.6%)--Tab. IV. These facts indicate the persistence of active natural foci in these regions. Serological investigations of the relatively great number of dogs from different regions of Slovakia showed that the presence of F. tularensis antibodies in this animal species, mainly in the watch dogs group, can be taken as a convenient marker or indicator of the existence of active natural foci of tularemia and as a suitable component for surveillance of this diseases.
Keywords: Tularemia; nemoci psů; psi; Czechoslovakia; Animals; Seroepidemiologic Studies; séroepidemiologické studie; Dogs; tularemie; zvířata; Dog Diseases; Československo